4(2x-2)=-2(x-6)

Simple and best practice solution for 4(2x-2)=-2(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-2)=-2(x-6) equation:



4(2x-2)=-2(x-6)
We move all terms to the left:
4(2x-2)-(-2(x-6))=0
We multiply parentheses
8x-(-2(x-6))-8=0
We calculate terms in parentheses: -(-2(x-6)), so:
-2(x-6)
We multiply parentheses
-2x+12
Back to the equation:
-(-2x+12)
We get rid of parentheses
8x+2x-12-8=0
We add all the numbers together, and all the variables
10x-20=0
We move all terms containing x to the left, all other terms to the right
10x=20
x=20/10
x=2

See similar equations:

| 2y’=6y+3 | | 4*x-7=19* | | 4x+1.5=60 | | (D^4+18D^2+81)=0y | | 10+8x3^x=42 | | 27-7=7y-27 | | 4x-7+8x=52 | | 4(4^2x)-17(4^x)-4=0 | | 4x-3x^2+0=0 | | 7x–4=x–16 | | 2x+31°.3x-26°=90° | | 1+2x=2–x^2 | | (5x)^2+8.5x=+20 | | (x+4)×(x+5)=x²-7 | | 2x+3+2x-1=0 | | (5x)2+8.5x=+20 | | 4x-5+2x+3=0 | | 5x=44+x | | 5=84+4x/8 | | x²=42 | | x3+17x2+16x=0 | | 5=84+4x/4 | | 4(8/4+3y/4)-3y=8 | | A=2,8,8,2eB=2,8,5 | | 0.97=x/(2.6x10^-8+x) | | 8x+5x+3x+2x=180 | | -3+6x=6 | | y^2-18y+81=9 | | T=5n-5 | | 6x+6×-1=60 | | 7a2+28a+24=0 | | t^2+2t+1=1 |

Equations solver categories